Ce-doped ZnO nanoparticles for efficient photocatalytic degradation of direct red-23 dye. Issue 6 (July 2015) - Kumar, R.; Umar, Ahmad; Kumar, G.; Akhtar, M.S.; Wang, Yao; Kim, S.H.
Abstract: This paper reports the simple, rapid and high-yield synthesis of Ce-doped ZnO nanoparticles using solution combustion method and its application for photocatalytic degradation. Several concentrations of Ce (0.5%, 1.39%, 2.55%, 3.28%, 3.71% and 4.14%) were doped into ZnO and the prepared nanoparticles were characterized by several techniques in terms of their morphological, structural, compositional, optical and photocatalytic properties. The detailed characterization studies revealed that the prepared Ce-doped ZnO nanoparticles are well-crystalline and possessing good optical properties. Further, the prepared Ce-doped ZnO nanoparticles were used as efficient photocatalyst for the photocatalytic degradation of harmful organic dye, i.e. direct red-23 (DR-23). From the detailed photocatalytic experiments, it was observed that Ce-doped ZnO nanoparticles are exhibiting appreciable photocatalytic activity and the degradation percentage was increased with increasing the concentration of Ce up to 3.28%; however, when the Ce concentration was further increased, the photocatalytic degradation was decreased. Thus, at optimum Ce concentration (3.28%), the prepared Ce-doped ZnO nanoparticles are exhibiting appreciable photocatalytic degradation (~99.5%) only in 70 min.